SARS-CoV-2 infection, clinical features and outcome of COVID-19 in United Kingdom nursing homes. Issue 3 (September 2020) - Graham, N.S.N.; Junghans, C.; Downes, R.; Sendall, C.; Lai, H.; McKirdy, A.; Elliott, P.; Howard, R.; Wingfield, D.; Priestman, M.; Ciechonska, M.; Cameron, L.; et al.
Summary: Objectives: To understand SARS-Co-V-2 infection and transmission in UK nursing homes in order to develop preventive strategies for protecting the frail elderly residents. Methods: An outbreak investigation involving 394 residents and 70 staff, was carried out in 4 nursing homes affected by COVID-19 outbreaks in central London. Two point-prevalence surveys were performed one week apart where residents underwent SARS-CoV-2 testing and had relevant symptoms documented. Asymptomatic staff from three of the four homes were also offered SARS-CoV-2 testing. Results: Overall, 26% (95% CI 22–31) of residents died over the two-month period. All-cause mortality increased by 203% (95% CI 70–336) compared with previous years. Systematic testing identified 40% (95% CI 35–46) of residents as positive for SARS-CoV-2, and of these 43% (95% CI 34–52) were asymptomatic and 18% (95% CI 11–24) had only atypical symptoms; 4% (95% CI −1 to 9) of asymptomatic staff also tested positive. Conclusions: The SARS-CoV-2 outbreak in four UK nursing homes was associated with very high infection and mortality rates. Many residents developed either atypical or had no discernible symptoms. A number of asymptomatic staff members also tested positive, suggesting a role for regular screening of both residents and staff in mitigating future outbreaks.